An Evaluation of the Foot Tapping Test (FTT) in a Healthy Population - Pribble, Brian (My University, 2017)
The reliability of the foot tapping test (FTT) has not been well identified in a normal healthy population. In order to make it clinically relevant, more research must be done on the FTT in healthy individuals in order to determine if it is a reliable measure of foot tapping ability. Purpose: The purpose of the study was to investigate the FTT in a healthy population using a variety of different measurement methods. By comparing the different measurement methods, we hope to make recommendations for future FTT research. Methods: 20 healthy individuals (10 male and 10 female), ages of 18-31, completed a series of foot tapping trials spread out over 4 separate visits. While seated, subjects tapped their foot repeatedly for 10 seconds while researchers counted the number of foot taps. The starting foot was randomized during each visit and each foot would be tested twice with the shoes ON and twice with the shoes OFF (resulting in 8 trials per visit * 4 visits = 32 trials per subject). The number of foot taps was determined with visual inspection, video playback (slowed and normal speed), and with the use of a force plate. The mean values of the FTT trials were compared across days, dominant vs. non-dominant foot, the shoes ON/OFF conditions, and with the different counting methods. Results: Significant differences were found in foot tapping rates in the shoes ON vs shoes OFF and dominant vs. non-dominant foot analyses (p<0.05). Furthermore it was found that a significant difference in the mean number of foot taps existed between visit 1 and the other 3 visits (p>0.05). It was found that the FTT exhibited high test-retest reliability (Pearson r >0.80) and high Cronbach’s alpha (alpha >0.80) across the live, slowed video counts, and force plate measurements for both the shoes ON and shoes OFF trials. Results allowed authors to make further suggestions for future FTT research
Keywords: Foot Tapping; FTT; Repetitive movements; Central drive